Analyzing student perceptions and behaviors in the use of an engaging visualization dashboard for peer code review activities - Duong, Hoang-Thanh; Huang, Chuan-Lin; Nguyen, Bao-An; Chen, Hsi-Min (Science of computer programming, 2026)
Traditional learning management systems often fail to sustain student motivation in computer science education, where consistent practice is crucial for skill development. This necessitates specialized tools that better support technical learning processes, foster engagement, and enable timely interventions for struggling students. This study introduces and evaluates a dashboard module integrated into peer code review activities within an "Object-Oriented Design Laboratory" course. The research analyzes comprehensive peer code review data collected through this dashboard to examine student review behaviors and identify at-risk students through behavioral indicators. A mixed-methods approach compared an experimental group (n = 75) using the assessment dashboard against a control group (n = 78) without dashboard access. Both cohorts received identical instructions over 17 weeks. Data collection included peer code review processes, programming exam results, and student surveys to analyze review behaviors and perceptions of the dashboard. Students with dashboard access demonstrated significantly improved engagement and self-awareness in the peer code review activity, along with measurable performance gains. Instructors benefited from more efficient monitoring capabilities across peer code review activities. Dashboard systems enhance metacognitive awareness through self-reflection and interaction monitoring, showing particular promise for programming education. These systems improve learning outcomes and instructional effectiveness by providing visual feedback that helps students track progress and identify improvement areas while giving instructors valuable insights into engagement patterns and learning behaviors.